2020
DOI: 10.1002/nau.24291
|View full text |Cite
|
Sign up to set email alerts
|

Do features of randomized controlled trials of pelvic floor muscle training for postprostatectomy urinary incontinence differentiate successful from unsuccessful patient outcomes? A systematic review with a series of meta‐analyses

Abstract: Aims: Efficacy of pelvic floor muscle training (PFMT) for postprostatectomy incontinence (PPI) differs between randomized clinical trials (RCT). This might be explained by variation in content/delivery of PFMT (eg, biofeedback, muscles targeted, and time of commencement of training). This review investigated whether outcome of meta-analysis differs based on presence or not of specific RCT features. Methods: PubMed, CINAHL, EMBASE, Physiotherapy Evidence Database (PEDro), and Cochrane were searched for RCTs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…It remains unclear whether the conclusion that pelvic floor training improves post-operative continence can be drawn at all, despite many studies existing up to date. A systematic review from 2020 showed in the long-term analysis that there was no difference in terms of PPI between patients who started pelvic floor exercises immediately postoperatively and the control group that did not perform any exercises ( 30 ). Similar results are reported by the 2015 Cochrane Review, in which there was no significant difference in the 12-month continence rate in 2.736 men between those who received PFME and/ or PMFT and those who did not (57% UI in the intervention group and 62% in the control group after 12 months (OR 0.85, 95% CI 0.60–1.22) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether the conclusion that pelvic floor training improves post-operative continence can be drawn at all, despite many studies existing up to date. A systematic review from 2020 showed in the long-term analysis that there was no difference in terms of PPI between patients who started pelvic floor exercises immediately postoperatively and the control group that did not perform any exercises ( 30 ). Similar results are reported by the 2015 Cochrane Review, in which there was no significant difference in the 12-month continence rate in 2.736 men between those who received PFME and/ or PMFT and those who did not (57% UI in the intervention group and 62% in the control group after 12 months (OR 0.85, 95% CI 0.60–1.22) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative PFM training could help prevent or reduce incontinence by improving the contribution of striated muscles to control continence 1 . Although some data question the efficacy of PFM training to improve continence after prostatectomy, 12 a recent systematic review showed that PFM training is more likely to be effective if it includes biofeedback (e.g., traditionally with electromyography, but also possible with ultrasound imaging), is focused on the urethral muscles (e.g., striated urethral sphincter) and begins before surgery 13 . Before the widespread use of TPUS in practice and research it is necessary to evaluate its clinimetric properties.…”
Section: Introductionmentioning
confidence: 99%
“…No benefit was however observed at the 6-month assessment. A recent 22-trial-meta-analysis showed significantly better outcomes for those trials where a preoperative PFME was performed [ 34 ]. A finer comprehension of its usefulness will however only be available when studies including standardized protocols of PFME will be carried out.…”
Section: Main Bodymentioning
confidence: 99%
“…, biofeedback, muscles targeted, and time of commencement of the training) and UC definition ( e.g. , 1 hour pad test, 24 hour pad test, International Consultation on Incontinence Questionnaire (ICIQ), bladder diary, and number of pads/d) ( Table 2 ) [ 34 ]. Over the past decade, several RCTs have been conducted to evaluate the effectiveness of PFME.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation